Analisis Kesalahan Penggunaan Bahasa Indonesia Pada Jurnal Ilmiah Pendidikan Geografi - Muftih, Anisa; Rahmadayanti, Rahmadayanti; Simamora, Angelina Setia; Marpaung, Viviana Br; Khairunnisa, Khairunnisa; Sipayung, Hadriadi Iskandar (Invention: Journal Research and Education Studies, 2025)
Writing a good and correct scientific journal is very important in the academic world, especially in the field of geography education. However, in practice, there are still many errors in the use of Indonesian language that are in accordance with applicable rules. This study aims to analyze various errors in the use of Indonesian language found in scientific journals of geography education, both in terms of morphology, syntax, and semantics. The method used in this study is qualitative descriptive analysis with a document study approach to a number of scientific journals of geography education published in recent years. The results of the study indicate that the most common errors found include the use of spelling that is not in accordance with the General Guidelines for Indonesian Spelling (PUEBI), ineffective sentence structures, inaccuracy in word choice, and the use of foreign terms that are not in accordance with the linguistic context. In addition, errors were also found in the use of punctuation and poor inter-paragraph coherence, which affects the readability and clarity of meaning in the scientific journal. Therefore, efforts are needed to increase awareness and understanding of academics, especially in the field of geography education, regarding the importance of using good and correct Indonesian language in scientific publications. Thus, the quality of scientific journals can be improved and can become a more credible source of reference in the academic world.